Comprehension of Indirect Requests Is Influenced by Their Degree of Imposition. Issue 2 (17th February 2018) - Stewart, Andrew J.; Le-luan, Elizabeth; Wood, Jeffrey S.; Yao, Bo; Haigh, Matthew
ABSTRACT: In everyday conversation much communication is achieved using indirect language. This is particularly true when we utter requests. The decision to use indirect language is influenced by a number of factors, including deniability, politeness, and the degree of imposition on the receiver of a request. In this article we report the results of an eye-tracking experiment examining the influence on reading of the degree of imposition of a request. We manipulate whether context describes a situation in which the level of imposition on the receiver of the request is high (which thus motivates the use of indirect language) with one in which the level of imposition is low (and thus does not motivate the use of indirect language). We compare the comprehension of statements that are phrased indirectly with the comprehension of statements that are phrased more directly. We find that statements phrased indirectly are read more quickly in contexts where the level of imposition on the receiver is high versus when the level of imposition is low. In contrast, we find the processing of statements phrased directly does not vary as a function of level of imposition. This indicates that readers use pragmatic knowledge to guide interpretation of indirect requests. Our data provide an insight into the interface between pragmatic and semantic processing.